Developing a Meaningful Learning Module Integrating Wasaka Character to Promote Environmental Awareness - Muhsinah Annisa; Fadhlan Muchlas Abrori; Teguh Prasetio; Rusmansyah; Herti Prastitasari; Eka Cahya Sari Putra (Jurnal Penelitian Pendidikan IPA, 2026)
Integrating local wisdom into learning is considered an effective strategy to strengthen character education and support meaningful learning. However, the integration of local cultural values into environmental learning materials for elementary school students remains limited. This study aimed to develop and evaluate a meaningful learning-based module integrating the Wasaka character (Waja Sampai Kaputing) to enhance students’ environmental awareness and environmental care attitudes. This study employed a Design-Based Research (DBR) approach adapted from Reeves’ model, consisting of problem analysis, solution development, iterative implementation, and reflection. The participants were 60 fifth-grade students of SDN Handil Bakti, Barito Kuala Regency, Indonesia. Data were collected through expert validation sheets, environmental awareness questionnaires, environmental care attitude scales, learning outcome tests, and teacher and student response questionnaires. The results showed that the developed module achieved high validity, with material validation of 91.42%, media validation of 88.57%, and language validation of 92%, indicating that the module was feasible for classroom implementation. The implementation results also showed positive learning outcomes and high levels of students’ environmental awareness and environmental care attitudes. These findings indicate that integrating meaningful learning with local cultural values can support environmental character education in elementary schools.